Studi Pengelolaan Drainase sebagai Upaya Mitigasi Bencana Banjir di Distrik Waisai Kabupaten Raja Ampat - Olga O Rumaropen; Yannice L M Sitorus; Anna M Labok; Asima Juliana (Badan Riset dan Inovasi Daerah (BRIDA) Provinsi Riau, 2026)
As the administrative center of Raja Ampat Regency, Waisai District is highly susceptible to recurrent flooding and urban inundation, which significantly disrupt the socio-economic activities of the community. Inundations reaching depths of 50–100 cm persist for several hours in specific locations on a near-annual basis during the rainy season, severely restricting public mobility. This study aims to evaluate the existing drainage system, identify the factors driving the degradation of drainage performance, and design an effective drainage management strategy to mitigate flood risks within the vulnerable areas of Waisai District. A mixed-methods approach (qualitative and quantitative) was employed, utilizing descriptive analysis and the SWOT method. Data were primarily collected through field observations and stakeholder interviews. The findings indicate that rapid urban development in Waisai has outpaced adequate and integrated drainage planning, leading to suboptimal channel capacities, particularly during high-intensity rainfall. The degradation of drainage functionality is predominantly driven by technical factors, alongside environmental and social aspects. The recommended approach lies within the WO (Weaknesses-Opportunities) quadrant, which emphasizes leveraging external opportunities—such as Waisai's status as a regency capital and a prominent marine tourism destination—to improve the capacity of government institutions in urban drainage planning and maintenance, as well as fostering community collaboration to address existing weaknesses. This research is expected to provide valuable insights for local governments in coastal urban areas in formulating policies for sustainable drainage management and disaster resilience.